Environment Aspect Impact Information System - Yap Yong Jing; Shahreen Kasim (Applied Information Technology And Computer Science, 2023)
The Web-Based Environment Aspect Impact system is a green building rating tool built for Sawit Kinabalu Sdn Bhd that helps to improve business processes that still use Excel sheets for manually filled assessments. The system was developed to enhance the business process of the operating unit in rating and recording aspects and impact, to carry out a comprehensive report, and to make the report comply with certification. The target user of the system is the operating unit, manager, and sustainability unit with 5 modules provided. This study uses agile scrum methodology and programming languages for system development, Laravel, and local server, and XAMPP as a database. This developed system can be able to help provide efficiency to the operating unit and staff while auditing the work activity